2014
DOI: 10.1042/bst20140007
|View full text |Cite
|
Sign up to set email alerts
|

Glycative stress and glyoxalase in kidney disease and aging

Abstract: Glycation is one of the important reactions regulating physiological state, and glycative stress, namely an overwhelming and unfavourable glycation state, is established as a pathological factor. Glycative stress is closely associated with not only various kidney diseases, but also kidney aging. Accumulating evidence, including studies in my laboratory, demonstrates that progression of renal tubular damage and its aging is correlated with the decrease in the activity of anti-glycative stress enzyme Glo1 (glyox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…WT expression)) for each of these functional categories of activity it was evident that a profound inhibitory activity towards ‘clock regulation’ was present in the input dataset (Figure S6B). Inspection of the individual transcripts coherently regulated across ILN/MLN/ spleen/thymus in GIT2KO mice demonstrated that, aside from the expected changes in immune-related factors (Btla [79], Tnfrsf4 [80], AI467606 [81]), there were significant reductions in multiple clock-related transcripts that are also associated with premature aging and DNA damage repair actions (DDR) (Per1 [22], Per2 [48], Tef [82], Dbp [83], LOC100044862-Fbxl3-like [84] as well as transcripts related to age-related stress/metabolism alterations and cell senescence (Glo1 [85], Ndufb10 [86], Ddit4 [87], Sin3a [88], Rnase4 [89] (Figure 7C). In addition to our LSI-based interpretation of the systemic effects of GIT2 genomic deletion we also individually annotated each significant GIT2KO dataset (ILN, MLN, spleen, thymus) using Ingenuity Pathway Analysis canonical signaling pathways (ILN Table S15; MLN Table S16; spleen Table S17, thymus Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…WT expression)) for each of these functional categories of activity it was evident that a profound inhibitory activity towards ‘clock regulation’ was present in the input dataset (Figure S6B). Inspection of the individual transcripts coherently regulated across ILN/MLN/ spleen/thymus in GIT2KO mice demonstrated that, aside from the expected changes in immune-related factors (Btla [79], Tnfrsf4 [80], AI467606 [81]), there were significant reductions in multiple clock-related transcripts that are also associated with premature aging and DNA damage repair actions (DDR) (Per1 [22], Per2 [48], Tef [82], Dbp [83], LOC100044862-Fbxl3-like [84] as well as transcripts related to age-related stress/metabolism alterations and cell senescence (Glo1 [85], Ndufb10 [86], Ddit4 [87], Sin3a [88], Rnase4 [89] (Figure 7C). In addition to our LSI-based interpretation of the systemic effects of GIT2 genomic deletion we also individually annotated each significant GIT2KO dataset (ILN, MLN, spleen, thymus) using Ingenuity Pathway Analysis canonical signaling pathways (ILN Table S15; MLN Table S16; spleen Table S17, thymus Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In CKD, it has been reported that renal tubular damage is correlated with a decrease in the activity of glyoxalase I in proximal tubule cells . Similar to the findings of previous research, MG was negatively correlated with eGFR in the present study and remained a predictive factor for outcomes in patients with CKD after adjusting for eGFR and other confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Vlassara et al [14] reported that administering AGE-modified rat albumin intravenously resulted in albuminuria and glomerulosclerosis. AGEs are also known to induce vascular calcification and endothelial dysfunction [15,16]. Immunohistochemical studies have shown that AGEs accumulate in the mesangial regions, glomerular capillary walls, and arterial walls of patients with diabetic nephropathy compared to those with healthy kidneys [17,18].…”
Section: Carbohydrate Metabolism and Ckdmentioning
confidence: 99%
“…AGE precursors including methylglyoxal and glyoxal are degraded by enzymes, such as glyoxase-1 (Glo-1), and eliminated from the body through the kidney [15,27]. Some previous reports have shown that activation of Glo-1 produces renal protective effects.…”
Section: Carbohydrate Metabolism and Ckdmentioning
confidence: 99%